Effectiveness of a multi-device 3D virtual environment application to train car service maintenance procedures - Borsci, Simone; Lawson, Glyn; Jha, Bhavna; Burgess, Mark; Salanitri, Davide (Springer Verlag, 2016)
This paper reports a study which demonstrates the advantages of using virtual-reality based systems for training automotive assembly tasks. Sixty participants were randomly assigned to one of the following three training experience to learn a car service procedure: i) observational training through video instruction; ii) an experiential virtual training and trial in a CAVE; and iii) an experiential virtual training and trial through a portable 3D interactive table. Results show that virtual trained participants, after the training, can remember significantly better (p <.05) the correct execution of the steps compared to video-trained trainees. No significant differences were identified between the experiential groups neither in terms of post-training performances nor in terms of proficiency, despite differences in the interaction devices. The relevance of the outcomes for the automotive fields and for the designers of virtual training applications are discussed in light of the outcomes, particularly that virtual training experienced through a portable device such as the interactive table can be effective, as can training performed in a CAVE. This suggests the possibility for automotive industries to invest in advanced portable hardware to deliver effectively long-distance programmes of training for car service operators placed all over the world.